Streamlining education processes: Lean management practices in Malaysian institutions / Mohd Faizal Bidin, Professor Dr. Jaafar Pyeman and Professor Dr Veera Pandiyan Kaliani Sundram - Bidin, Mohd Faizal; Pyeman, Jaafar; Kaliani Sundram, Veera Pandiyan (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
The education sector plays a crucial role in shaping the future of a country. In Malaysia, the government has consistently prioritized education since the nation's independence. In the latest budget, Prime Minister Datuk Seri Anwar Ibrahim allocated RM 55.2 billion, the largest amount, to education in 2023. This substantial allocation reflects the government's strong commitment to the development of the education sector. Nevertheless, incorporating lean management practices in education can be challenging as it requires a shift in mindset and culture. Lean management focuses on eliminating waste and continuously improving processes, which may clash with traditional educational structures and practices. Additionally, the data-driven decision-making approach emphasized by lean management might not align with the subjective evaluation methods often used in educational institutions. Despite these obstacles, several universities have managed to implement lean management principles successfully, leading to enhanced efficiency and effectiveness. To successfully implement lean management in education, a primary focus should be on waste reduction. Educational institutions, such as schools and universities, often generate substantial amounts of paper waste through activities like exams and applications. In Malaysia, universities alone produce approximately 70,000 tons of waste annually, much of which could be recycled. One effective approach to minimize paper and recyclable waste is by digitizing traditional processes. Memos, application forms, and documents can be converted into digital formats, and an efficient system can be established to streamline the process while fostering a culture of change within the organization. Additionally, implementing a ban on single-use plastics on campus could significantly reduce waste and propel the institution towards a more sustainable future. Lean management involves a continuous improvement process, where small changes are made over time to achieve better outcomes. In the context of education, this entails regularly assessing student learning and instructional practices while providing ongoing professional development for teachers and staff. The Covid-19 pandemic has accelerated digital transformation in Malaysia, leading many universities to adopt blended learning and digital assessment using tools like Learning Management systems.